(untitled) (New York, NY., 1966)
Yukichi Fukuzawa (1835-1901) was a leading figure in the cultural revolution that transformed Japan from an isolated feudal nation into a full-fledged player in the modern world. He translated a wide range of Western works and adapted them to Japanese needs, inventing a colorful prose style close to the vernacular. He also authored many books, which were critical in introducing the powerful but alien culture of the West to the Japanese. Only by adopting the strengths and virtues of the West, he argued, could Japan maintain its independence despite the "disease" of foreign relations.
Keywords: Fukuzawa, Yukichi,Educators; Biography; 1835-1901; Japan